2017
DOI: 10.1093/geront/gnw154
|View full text |Cite
|
Sign up to set email alerts
|

Social Connectedness, Perceived Isolation, and Dementia: Does the Social Environment Moderate the Relationship Between Genetic Risk and Cognitive Well-Being?

Abstract: The results support the need to consider the social context when examining cognitive well-being in later life. These findings also indicate a need for the development of policies and services that promote a rich social environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Contrary to our expectations social networks and the APOE e4 allele were unrelated and no interactions between them were found to be significantly associated with dementia. Hence, in line with the results presented by Brenowitz et al (2014) and Zuelsdorff et al (2013), but in contrast to those of Niti et al (2008) and Poey et al (2017), strong social networks do not seem to moderate the increased risk of dementia implied by the APOE e4 allele.…”
Section: Allsupporting
confidence: 79%
See 1 more Smart Citation
“…Contrary to our expectations social networks and the APOE e4 allele were unrelated and no interactions between them were found to be significantly associated with dementia. Hence, in line with the results presented by Brenowitz et al (2014) and Zuelsdorff et al (2013), but in contrast to those of Niti et al (2008) and Poey et al (2017), strong social networks do not seem to moderate the increased risk of dementia implied by the APOE e4 allele.…”
Section: Allsupporting
confidence: 79%
“…Among those, neither Brenowitz, Kukull, Beresford, Monsell, and Williams (2014), who investigated the incidence of mild cognitive impairment, nor Zuelsdorff et al (2013), who examined a sample of individuals with a family history of AD, could verify interactions between aspects of social relationships and the APOE e4 allele. In contrast, Poey, Burr, and Roberts (2017) found that living arrangements and perceived social support could moderate the association between the APOE e4 allele and cognitive function. Moreover, Niti, Yap, Kua, Tan, and Ng (2008) found that different kinds of leisure activities (including social activities) protected against cognitive decline and that the protective impact was particularly strong among individuals carrying the APOE e4 allele.…”
Section: Social Network and The Apoe E4 Allelementioning
confidence: 77%
“…Earlier studies on social factors and cognitive decline in middle‐ and older‐aged adults have commonly followed a single measurement approach . Among the few ones in which researchers examined social isolation and loneliness simultaneously, the evidence has yielded mixed results . For instance, findings from the English Longitudinal Study of Ageing revealed that social isolation was related to decreased episodic memory and verbal fluency after a 4‐year follow‐up period, whereas loneliness was found to be associated with poorer immediate and delayed recall over time .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Among the few ones in which researchers examined social isolation and loneliness simultaneously, the evidence has yielded mixed results. 10,[16][17][18][19][20] For instance, findings from the English Longitudinal Study of Ageing revealed that social isolation was related to decreased episodic memory and verbal fluency after a 4-year follow-up period, whereas loneliness was found to be associated with poorer immediate and delayed recall over time. 17 By contrast, Wilson et al, 21 using data from a longitudinal cohort study of 823 older adults, reported that loneliness was linked to a more rapid decline in semantic memory rather than episodic memory.…”
Section: Introductionmentioning
confidence: 99%
“…The act of talking with someone is a fundamental action for building social connectedness and reducing the feeling of social isolation. Social disconnectedness and perceived social isolation are likely to cause health risks [1][2][3], such as dementia [4,5], depression [6], and early death [7]. Therefore, it is important to increase opportunities for elderly people to have dialogues with other people.…”
Section: Introductionmentioning
confidence: 99%